2020
DOI: 10.18502/cmm.6.1.2504
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenicity and Phylogeny of Aspergillus section Flavi in poultry feed in Iran

Abstract: Background and Purpose: This study was conducted to evaluate the presence of aflatoxigenic strains and level of aflatoxin in poultry feed. Aflatoxigenic strains were investigated in corn and soybean meal as the ingredients of poultry feed, as well as in two types of commercial feed, namely pellet and mash. The gene sequencing was performed to identify the species of Aspergillus section Flavi. Materials and Methods: All samples were randomly collected from feed storage silos located in Iran in 2018. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The predominant Aspergillus species observed during the study was A. flavus (39.1%). This is in agreement with the findings of Fapohunda et al (2012), Davari et al (2015), Fakruddin et al (2015 and Ghaemmaghami et al (2016Ghaemmaghami et al ( , 2020 who reported Aspergillus section flavi to be the predominant species for producing aflatoxins in various feeds. This might have been that A. flavus can adapt to different geographical locations especially the sub-tropical and tropical regions of a country.…”
Section: Reverse White To Brown a Terreussupporting
confidence: 92%
“…The predominant Aspergillus species observed during the study was A. flavus (39.1%). This is in agreement with the findings of Fapohunda et al (2012), Davari et al (2015), Fakruddin et al (2015 and Ghaemmaghami et al (2016Ghaemmaghami et al ( , 2020 who reported Aspergillus section flavi to be the predominant species for producing aflatoxins in various feeds. This might have been that A. flavus can adapt to different geographical locations especially the sub-tropical and tropical regions of a country.…”
Section: Reverse White To Brown a Terreussupporting
confidence: 92%
“…Consistent with the present study, 81.08% of aflatoxigenic Aspergillus species were reported in grain feeds (Salisu et al, 2020). However, a lower frequency of aflatoxigenic Aspergillus species was reported in dairy feed (52%) from Katsina State of Nigeria, animal feed from Algeria (68.4%), and dairy feed (25%) obtained from the Fulani province in South Africa (Ghaemmaghami et al, 2016;Salisu et al, 2020). Moreover, a comparable aflatoxigenic Aspergillus species (70%) was found in poultry feeds collected from Tehran and Alborz provinces (Ghaemmaghami et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…During the transfer of pellets from the Pelletizer machine to the cooling machine, exposure to saprophytic Aspergillus in the environment can lead to growth during storage. Malfunctions in the equipment can also impact the feed preparation process, potentially affecting the overall quality ( Ghaemmaghami et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Ghaemmaghami et al (2016) conducted a study to determine the levels of fungal contamination in poultry feed. The research identified a total of 384 fungal isolates across different feed ingredients, including corn (124 isolates), soybean meal (92 isolates), mash feed (72 isolates), and pellet feed (96 isolates).…”
Section: Discussionmentioning
confidence: 99%